Self-Representation in an Expanded Field From Self-Portraiture to Selfie, Contemporary Art in the Social Media Age - Lehner, Ace (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Defined as a self-image made with a hand-held mobile device and shared via social media platforms, the selfie has facilitated self-imaging becoming a ubiquitous part of globally networked contemporary life. Beyond this selfies have facilitated a diversity of image making practices and enabled otherwise representationally marginalized constituencies to insert self-representations into visual culture. In the Western European and North American art-historical context, self-portraiture has been somewhat rigidly albeit obliquely defined, and selfies have facilitated a shift regarding who literally holds the power to self-image. Like self-portraits, not all selfies are inherently aesthetically or conceptually rigorous or avant-guard. But, -as this project aims to do address via a variety of interdisciplinary approaches- selfies have irreversibly impacted visual culture, contemporary art, and portraiture in particular. Selfies propose new modes of self-imaging, forward emerging aesthetics and challenge established methods, they prove that as scholars and image-makers it is necessary to adapt and innovate in order to contend with the most current form of self-representation to date. The essays gathered herein will reveal that in our current moment it is necessary and advantageous to consider the merits and interventions of selfies and self-portraiture in an expanded field of self-representations. We invite authors to take interdisciplinary global perspectives, to investigate various sub-genres, aesthetic practices, and lineages in which selfies intervene to enrich the discourse on self-representation in the expanded field today. Ace LehnerEditor